Water users' attitudes towards fish-protection screens: a case study from Australia's Murray-Darling (Baaka) Basin. Issue 1 (2nd January 2023) - Nayeem, Tahmid; Pawsey, Nick; Baumgartner, Lee; Sexton, Amie; Boys, Craig
ABSTRACT: Fish-protection screens for water pumps and channels can conserve fish populations and deliver operational benefits to irrigators. However, the uptake of fish screens is mixed, and there is limited evidence concerning irrigator attitudes towards this technology. The current study addresses this knowledge deficit through 26 semi-structured in-depth interviews with irrigators and other associated water users. The purpose of this study was to understand pump screening practices and experiences, the current level of awareness of fish-screening options, attitudes towards potential environmental and financial benefits, overall intentions to install fish screens, the role of attitudes and other factors in impacting these intentions, and critical fish screening knowledge gaps and communication preferences. Drawing on the theoretical framework of Diffusion of Innovations (DOI), the study identified that irrigators have low awareness of native fish loss and the benefits of fish screening. However, they are interested in learning more about the economic, social, and environmental benefits of fish screen adoption. Customised communications and education programs are needed to increase intentions to install fish screens in Australia.